The Algorithms of Preliminary Processing of the Inclinometric Control Data during the Monitoring of the Building - V. Grecheneva, A.; O.R. Kuzichkin, Prof.; N.V. Dorofeev, Prof.; I. Surzhik, D. (International Journal of Engineering and Technology, 2018)
The article is devoted to the development of algorithmic support of the inclinometric control system built on the basis of accelerometers using the phase-metric method. This system is used to automated control the deviation of the angular parameters of the building axis from the vertical. An algorithm for data collection and transmission has been developed that allows automatic data collection from the accelerometer network via the 802.11 b/n/g interface. An algorithm for calculating the angle of deviation of the building axes from the vertical is developed on the basis of the phase-metric method. According to this algorithm for determining the angle, it is necessary to register the moments of crossing the reference signal zero and the signal of the accelerometers are fixed along the construction axes. The time difference of the zero values of the signals in each of the periods will be equal to the deviation angle of the building axis from the vertical. To implement the phase-metric method of angle measurement, an algorithm is developed for the sub-program of the zero-crossing detector. This algorithm describes the sequence of operations of comparing signals for the transition of the value of the signal parameters from positive to negative and vice versa. In the final section, the error of the developed software implemented in the experimental inclinometer installation was estimated.